Case Report: Anti-NMDA Receptor Encephalitis With Bilateral Hearing Loss as the Initial Symptom - Cheng, Hongjiang; Yang, Fengbing; Zhang, Jing; Xu, Lina; Jia, Longbin; Zhao, Doudou; Liu, Wei; Li, Huimin (Frontiers in Neurology, 2021)
Introduction: Anti-N-methyl-d-aspartate receptor (anti-NMDAR) encephalitis is an autoimmune disease associated with the NMDA receptor. This paper describes a patient who presented with bilateral hearing loss as the initial symptom of anti-NMDAR encephalitis. Case Report: we describe a 31-year-old young female with anti-NMDAR encephalitis who presented with complete bilateral hearing loss after brief loss of consciousness,then accompanied with other symptoms,such as generalized tonic-clonic seizures,manic episodes,excessive salivation,severe cognitive impairment and complex nonconvulsive status epilepticus.Great improvement was achieved by a combined treatment of steroid,IVIG and plasmapheresis,especially after surgical removal of ovarian teratoma.When she was discharged on hospital day 43, her hearing loss obtained a significant improvement. Conclusion: This case study and literature review investigated the impairment of hearing loss and its subsequent treatment in patients with anti-NMDAR encephalitis.